2018
DOI: 10.1080/14767058.2018.1443072
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia detection in low birth weight neonates using a novel bracelet device

Abstract: The BEMPU Bracelet is an accurate screening tool to detect and alert for neonatal hypothermia, thereby facilitating prompt management, which could prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Currently only one study has been conducted to determine the accuracy of the TempWatch in detecting hypothermia. Tanigasalam et al ( 84 ) compared the TempWatch to mercury-in-glass axillary thermometry and reported it to have a sensitivity of 98.6% and specificity of 95% in detecting hypothermia. However, only neonates weighing <2,000 g were included in this study and the TempWatch was only worn for 24 h. Therefore, further studies are needed to determine whether this accuracy is applicable to neonates weighing 2,000 g or more and if the accuracy is maintained throughout the entire 30 days that the device is marketed for ( 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently only one study has been conducted to determine the accuracy of the TempWatch in detecting hypothermia. Tanigasalam et al ( 84 ) compared the TempWatch to mercury-in-glass axillary thermometry and reported it to have a sensitivity of 98.6% and specificity of 95% in detecting hypothermia. However, only neonates weighing <2,000 g were included in this study and the TempWatch was only worn for 24 h. Therefore, further studies are needed to determine whether this accuracy is applicable to neonates weighing 2,000 g or more and if the accuracy is maintained throughout the entire 30 days that the device is marketed for ( 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, the Bempu bracelet achieved a sensitivity and specificity of 98.5% and 95%, respectively, when compared to axillary temperatures in a sample size of 2,424 alarm events. 256 The Bempu is commercially available, but at $29.76 purchase price at the time of publication, is not affordable in low-resource settings. In addition, its current battery lasts for one month and is non-replaceable.…”
Section: Diagnostics For Neonatal Healthmentioning
confidence: 99%
“…Hypothermia is a common occurrence in postnatal wards and step-down nurseries of resource-restricted health care systems [7].In community-based studies in Nepal and India, hypothermia prevalence ranged from 11% to 92% [8]. The risk of hypothermia and related morbidities is the highest in the first week of life [9].…”
Section: Introductionmentioning
confidence: 99%
“…In lowresource settings, the facilities for thermal monitoring and thermal protection of neonates are limited. The BEMPU Bracelet is an accurate device that can be used in low-resource settings to detect and alert for neonatal hypothermia with significant sensitivity and specificity [7]. The BEMPU Bracelet is a silicone band with a thermistor metal cup to detect a neonate's temperature.…”
Section: Introductionmentioning
confidence: 99%